[latex] \sqrt{} \sqrt{3} \sqrt[3]{9} [/latex]÷[latex] \sqrt[4]{27} [/latex] плес

[latex] \sqrt{} \sqrt{3} \sqrt[3]{9} [/latex]÷[latex] \sqrt[4]{27} [/latex] плес
Гость
Ответ(ы) на вопрос:
Гость
=(3^(1/2)*9^(1/6)^(1/2)/27^(1/4)=(3^(1/2)*3^(1/3))^(1/2)/27^(1/4)= =(3^(5/6))^(1/2)/3^(3/4)=3^(5/12)/3^(3/4)=3^(5/12-3/4)=3^(-1/3)=1/∛3. ∛9=3^(2/3) √((3^1/2)*3(2/3))=√(3^(1/2+2/3))=√(3^(5/6))=3^(5/6)^(1/2)=3^(5/12) 27^(1/4)=3^(3/4) 3^(5/12)/3^(3/4)=3^(5/12-3/4)=3^(-1/3)=1/∛3.
Не нашли ответ?
Ответить на вопрос
Похожие вопросы